Combining simulation and animation of queueing scenarios in a flash-based discrete event simulator - Khalid, Ruzelan; Kreutzer, Wolfgang; Bell, Tim (Springer Berlin Heidelberg, 2009)
eLearning is an effective medium for delivering knowledge and skills to scattered learners.In spite of improvements in electronic delivery technologies, eLearning is still a long way away from offering anything close to efficient and effective learning environments.Much of the literature supports eLearning materials which embed simulation will improve eLearning experience and promise many benefits for both teachers and learners.This paper presents an application framework for Discrete Event Simulation (DES), written in Adobe Flash and its ActionScript 2 scripting language.Based on the framework, a set of DES components has been designed and constructed to ease both construction and embedding of multimedia enriched and animated DES models into web-based eLearning environments.